Impact of medium-term conservation agriculture on maize (Zea mays L.) yield and soil nutrient dynamics in the Terai region of West Bengal - Shahajahan, M; Sushovan, P; Ashok, C; Abhas, S K; Sagardeep, S (Plant Science Today, 2026)
Conservation agriculture (CA) is widely recognized as a sustainable approach to maintaining soil health, improving crop productivity and mitigating environmental challenges associated with conventional farming practices. The study was conducted to evaluate the effects of CA practices on maize yield and soil fertility in the seventh year of medium-term experiment. Seven experimental treatment combinations of varying amounts of crop residue (0, 3 and 5 t ha-1) and fertilizer doses (RDF, 160 kg N ha-1 with recommended PK and 200 kg N ha-1 with recommended PK) have been applied under zero tillage condition in the present study. Field experiment compared the effects of different treatments to on plant height, cob length, seed index, kernel count, cob weight, grain yield, stover yield and soil nutrient distribution at three soil depths (0-10, 10-20 and 20-40 cm). The treatment with highest residue load and nitrogen, showed the most significant improvements in crop parameters, recording the tallest plants (305.43 cm), longest cobs (18.63 cm), highest seed index (31.10), maximum kernels per row (27), heaviest cobs (25.74 g) and superior grain yield (9.77 t/ha) and stover yield (10.58 t/ha) along with higher soil available nitrogen and potassium content. Although, soil organic carbon (SOC) increased significantly in the surface soil (0-10 cm), particularly in highest residue load but recommended N level (1.03 %), while changes in deeper layers were not statistically significant. CA methods have little effect on soil pH. This reflects the importance of appropriate management of residue and soil nutrients for sustainable crop production.